PSIII-2 Infrared technology: A potential tool for improved pork production. (8th October 2021) - Ereke, Samuel O; Brown, Jennifer; Roy, Cyril; Phyllis, Shand; Predicala, Bernardo; Cook, Nigel
Abstract: This study investigated infrared technology (IRT) as a non-invasive tool for identifying febrile or stressed pigs before slaughter. A total of 120 market pigs (BW= 105.1 ± 4.9 kg) were transported in five replicate trips (20–25 pigs/replicate) for 2 hr to an abattoir during summer 2020. Ocular and body temperatures of the pigs were recorded using a consumer grade digital infrared camera (FLIR C3, FLIR Systems) in lairage immediately after transport. Thermographic images were taken from 0.25m and 2m from pigs' eyes and body (back/flank), respectively. At slaughter, blood samples were collected from each animal for cortisol, glucose and lactate analyses. Carcass pH measures were taken at 1 and 3 h post-mortem and loin samples were collected for meat quality assessment. Linear regression models (SAS 9.4) were used to evaluate whether post-transport temperature was predictive of blood and meat quality responses using ambient temperature and relative humidity as covariates. There were significant relationships between pigs' ocular and body temperatures and blood measures. The regression coefficient (r 2 ) of ocular temperatures for blood cortisol, glucose and lactate were 0.15, 0.15 and 0.04, respectively (P ≤0.03). There were significant relationships between pig ocular temperatures and pH taken at 1, 3 and 24 h post-mortem (r 2 =0.32, 0.18 and 0.51 respectively, P < 0.001). Meat yellowness (b*) and drip loss increased with body temperatures [r 2 =0.12 (P =0.0002) and 0.05 (P = 0.024), respectively]. Results for Warner-Bratzler shear force showed that higher temperatures were associated with tougher meat (ocular temperature: r 2 =0.51, P < 0.0001). In conclusion, as pig temperature increased, blood stress markers and drip loss increased and pH at 1 and 3 h post-mortem decreased, indicative of pale, soft and exudative (PSE) meat traits. IRT shows potential for identifying diseased/stressed pigs prior to slaughter and could be a valuable tool for improved food safety and meat quality.